2023
DOI: 10.1111/psyp.14247
|View full text |Cite
|
Sign up to set email alerts
|

Theta and alpha power track the acquisition and reversal of threat predictions and correlate with skin conductance response

Abstract: The ability to flexibly adjust one's threat predictions to meet the current environmental contingencies is crucial to survival. Nevertheless, its neural oscillatory correlates remain elusive in humans. Here, we tested whether changes in theta and alpha brain oscillations mark the updating of threat predictions and correlate with response of the peripheral nervous system. To this end, electroencephalogram and electrodermal activity were recorded in a group of healthy adults, who completed a Pavlovian threat con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 100 publications
(154 reference statements)
0
12
1
Order By: Relevance
“…Although this research presents some of the first data using EEG and desktop virtual reality to examine event-related oscillatory responses and behavioral dynamics during threat imminence, future research may address some of the study's limitations. First, even though previous studies have observed a link between frontal midline theta and threat processing (Chen et al, 2021;Chien et al, 2017Chien et al, , 2020Chirumamilla et al, 2019;Starita et al, 2023), we failed to observe CS-related frontal midline theta activity in the RRI task. Instead, we found the CS evoked a large theta response over right posterior regions of the scalp (e.g., channels P8 and P4).…”
Section: Directionscontrasting
confidence: 88%
See 1 more Smart Citation
“…Although this research presents some of the first data using EEG and desktop virtual reality to examine event-related oscillatory responses and behavioral dynamics during threat imminence, future research may address some of the study's limitations. First, even though previous studies have observed a link between frontal midline theta and threat processing (Chen et al, 2021;Chien et al, 2017Chien et al, , 2020Chirumamilla et al, 2019;Starita et al, 2023), we failed to observe CS-related frontal midline theta activity in the RRI task. Instead, we found the CS evoked a large theta response over right posterior regions of the scalp (e.g., channels P8 and P4).…”
Section: Directionscontrasting
confidence: 88%
“…To date, several EEG and MEG studies have identified two event-related oscillatory signals theta and gamma associated with fear conditioning. With regard to the former signal, EEG oscillations in the theta frequency range (4-8 Hz) recorded over frontal midline (Balconi & Lucchiari, 2008;DeLaRosa et al, 2014;Gonzalez-Escamilla et al, 2023) and posterior (Aftanas et al, 2001(Aftanas et al, , 2002(Aftanas et al, , 2004DeLaRosa et al, 2014;Gonzalez-Escamilla et al, 2023;Luther et al, 2022;Sun et al, 2012) areas of the scalp following the onset of an aversive cue/stimulus have been associated with cognitive processes related to fear learning (Chen et al, 2021;Chien et al, 2017Chien et al, , 2020Chirumamilla et al, 2019;Starita et al, 2023) and recall ( [Bierwirth et al, 2021;Mueller et al, 2014;Sperl et al, 2018] -but see [Bierwirth et al, 2023] for null results). With respect to the latter signal, event-related gamma activity (30-60 Hz) recorded over occipital and somatosensory areas of the scalp regions have been observed shortly after the onset of a conditioned stimulus (Miskovic & Keil, 2012;Santos-Mayo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In a few of the cases, right-handed people are preferred [18], [21], [22], [25], [39]- [41], [44], [45], [50], [51], [53]- [57]. Subject's consent is also taken in some literature [21], [22], [24], [26]- [35], [37]- [43], [45]- [47], [52], [54], [56], [58]- [62]. Meanwhile, there is no information about the consent in other remaining studies.…”
Section: B Subject Informationmentioning
confidence: 99%
“…Some of the most used stimuli are musical videos [18], [48], [63]- [65], visual stimuli [23], [40], [41], [45], [53], [54], [67], images [31], [33], [36], [46], [50], [51], [68], [69], Audio [29], [34], [37], [52], task based stimuli [24], [25], [27], [38], [39], [42]- [44], [48], [55]- [57], [58], [62], [70]- [75], film clips [76], [77], normal video clips [26], [62], [78]. In task-based stimuli either the subjects are instructed to do the mental task (mathematics-related problems, memorizing, computer-based gaming, and reading) or physical task (coldpressor test, rope skipping, surgical task, and fatigue exercise).…”
Section: Stimulation Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation